Local structure of Ge quantum dots determined by combined numerical analysis of EXAFS and XANES data. (3rd December 2015) - Zhang, Yuanpeng; Ersoy, Osman; Karatutlu, Ali; Little, William; Sapelkin, Andrei
Abstract : The sensitivity of X‐ray absorption near‐edge structure (XANES) to the local symmetry has been investigated in small (∼4 nm) matrix‐free Ge quantum dots. The FDMNES package was used to calculate the theoretical XANES spectra that were compared with the experimental data of as‐prepared and annealed nanoparticles. It was found that XANES data for an as‐prepared sample can only be adequately described if the second coordination shell of the diamond‐type structural model is included in the FDMNES calculations. This is in contrast to the extended X‐ray absorption fine‐structure data that show only the first‐shell signal. These results suggest that, despite the high degree of disorder and a large surface‐to‐volume ratio, as‐prepared small Ge quantum dots retain the diamond‐type symmetry beyond the first shell. Furthermore, we utilized this sensitivity of XANES to the local symmetry to study annealed Ge quantum dots and found evidence for significant structural distortion which we attribute to the existence of surface disorder in the annealed oxygen‐free Ge quantum dots.